2018
DOI: 10.1111/bcp.13564
|View full text |Cite
|
Sign up to set email alerts
|

Trends in analgesic consumption in France over the last 10 years and comparison of patterns across Europe

Abstract: Paracetamol consumption is clearly highest in France, whereas its use of strong opioids is among the lowest in Europe, although its consumption of oxycodone has increased significantly. Further studies are required specifically to monitor these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 46 publications
(62 reference statements)
11
109
1
3
Order By: Relevance
“…A questionnaire‐based study addressing the risk of misuse and dependence on nonprescription analgesics in French community pharmacies indicates a rate of misuse of codeine close to 7%, while no misuse emerged from the answers of the 107 individuals taking paracetamol (Roussin, Bouyssi, Pouché, Pourcel, & Lapeyre‐Mestre, ). This is in accordance with a more recent study showing that paracetamol, whose consumption is particularly high in France in comparison with other Western European countries (Hider‐Mlynarz, Cavalié, & Maison, ), was correctly used in terms of indication, dosing and frequency by 86% of individuals (Severin et al, ). A cross‐sectional survey based on telephone interviews of nearly 2,000 Australian OTC drug consumers showed that 96% were using paracetamol appropriately, while they were 69% regarding NSAIDs (Stosic, Dunagan, Palmer, Fowler, & Adams, ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A questionnaire‐based study addressing the risk of misuse and dependence on nonprescription analgesics in French community pharmacies indicates a rate of misuse of codeine close to 7%, while no misuse emerged from the answers of the 107 individuals taking paracetamol (Roussin, Bouyssi, Pouché, Pourcel, & Lapeyre‐Mestre, ). This is in accordance with a more recent study showing that paracetamol, whose consumption is particularly high in France in comparison with other Western European countries (Hider‐Mlynarz, Cavalié, & Maison, ), was correctly used in terms of indication, dosing and frequency by 86% of individuals (Severin et al, ). A cross‐sectional survey based on telephone interviews of nearly 2,000 Australian OTC drug consumers showed that 96% were using paracetamol appropriately, while they were 69% regarding NSAIDs (Stosic, Dunagan, Palmer, Fowler, & Adams, ).…”
Section: Resultssupporting
confidence: 89%
“…In this respect, a systematic review of the literature coupled with a meta-analysis included five randomized clinical trials corresponding to an overall assessment of one thousand patients with chronic pain resulting from multiple aetiologies, headache/migraine or knee osteoarthritis and followed for at least 3 months (Hadi, Alldred, Briggs, Munyombwe, & Closs, 2014). Interventions consisted in face-to-face or telephonebased medication review and, in one study, recommendations to GPs (Gammaitoni et al, 2000;Hay et al, 2006;Marra et al, 2012). The analysis demonstrated that pharmacist-led medication was associated with a significant decrease in pain intensity and an improvement of both physical functioning and patient satisfaction.…”
Section: Pharmacists Interventions In Analgesic Otc: Rationale Objmentioning
confidence: 99%
“…We can even notice that if older people (≥85 years) remained the most exposed to atropinics between 2006 and 2015, these patients had the most pronounced atropinic burden decrease. Secondly, dextropropoxyphene was the most used drug before 2010 . These high percentages of use explain the major impact observed after the changes in its regulatory status, even if these regulatory measures were not directly related to their atropinic properties.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011 and 2014, new guidelines restricted the use of domperidone due to the risk of cardiac events, with a particular focus on elderly: Thus, domperidone was not recommended for people aged 60 years and over . Thirdly, dextropropoxyphene withdrawal led to a switch toward paracetamol, tramadol, codeine, and opium powder in elderly people with chronic pain as well as in the general population .…”
Section: Discussionmentioning
confidence: 99%
“…Other countries typically did not use strong opioids for pain relief or tended to place greater restrictions on their use. For example, France has relatively high consumption of painkillers, but it consumes primarily non‐opioids and has very low use of strong opioids (Hider‐Mlynarz, Cavalie, and Maison ). Prior to 2008, Norway did not reimburse opioids for non‐cancer pain (Hamunen et al.…”
Section: Factors Contributing To High Us Drug Overdose Mortalitymentioning
confidence: 99%